2021
DOI: 10.1186/s12891-021-04069-z
|View full text |Cite
|
Sign up to set email alerts
|

Criterion validity of The International Physical Activity Questionnaire-Short Form (IPAQ-SF) for use in clinical practice in patients with osteoarthritis

Abstract: Background To tailor physical activity treatment programs for patients with osteoarthritis, clinicians need valid and feasible measurement tools to evaluate habitual physical activity. The widely used International Physical Activity Questionnaire-Short Form (IPAQ-SF) is not previously validated in patients with osteoarthritis. Purpose To assess the concurrent criterion validity of the IPAQ-SF in patients with osteoarthritis, using an accelerometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…The International Physical Activity Questionnaire (IPAQ-SF) was used to assess PA in its short form. It followed the classification indicated in several studies ( 24 28 ) and agreed with the official IPAQ classification protocol (www.ipaq.ki.se) ( 29 ), in which individuals are classified in three PA levels. These levels are calculated based on the duration (minutes), frequency per week, and MET intensity (MET.min/week); this value is obtained through a weighted approximation of the total PA performed during 1 week ( 27 ).…”
Section: Methodsmentioning
confidence: 62%
“…The International Physical Activity Questionnaire (IPAQ-SF) was used to assess PA in its short form. It followed the classification indicated in several studies ( 24 28 ) and agreed with the official IPAQ classification protocol (www.ipaq.ki.se) ( 29 ), in which individuals are classified in three PA levels. These levels are calculated based on the duration (minutes), frequency per week, and MET intensity (MET.min/week); this value is obtained through a weighted approximation of the total PA performed during 1 week ( 27 ).…”
Section: Methodsmentioning
confidence: 62%
“…However, our study population included elderly people over 70 years old. This data collection tool has only recently been used in clinical practice to evaluate this age group ( 27 , 28 ). Fourth, the COVID-19 infection rate was lower and measures employed in the study area less stringent than those in Western countries and other regions with government-enforced lockdowns and quarantines.…”
Section: Discussionmentioning
confidence: 99%
“…The IPAQ-SF comprises seven open-ended questions concerning individuals’ recollection of their physical activity during the last 7 days [ 79 ]. One study confirmed the validity and reliability of the IPAQ-SF for older adults with osteoarthritis [ 80 ]. Each type of activity was transformed into a metabolic equivalent (MET) score, which was defined elsewhere [ 81 ].…”
Section: Methodsmentioning
confidence: 97%